MAJORING INFLUENCE ON THE DIET QUALITY IN UNIVERSITY STUDENTS - Bolshakova , Larisa; Ladnova , Olga; Izvekova , Elena; Ashihina, Ludmila; Merkulova , Elena; Kuzina , Alina (Revista Inclusiones, 2020)
Disordered eating in students is often associated with the lack of knowledge on these issues. The purpose of the present study was to identify the association between diet quality of the students, their majoring and their competence in nutritiology. The comparative analysis of dietary habits, energy and macronutrientin take and eating behaviour in students, who majored in nutrition technology (NTD) and in economics (ED), was performed. Food diaries were analyzed, questionnaire survey and testing was conducted among 187 male and female first year and fourth year students from the Orel State University of Economics and Trade. Statistical analysis was conducted by Wilcoxon T-test, MannWhitney U-test, Pearson's χ 2 -test and McNemar's test. The results of the study showed that first year NTD and ED students lacked protein and had excessive amount of fats and carbohydrates in their diet, energy value exceeded the norm. Fourth year NTD students protein consumption was 3.9 % below the norm, ED students – 15.4 % below the norm. Fats and carbohydrates content exceeded the normal values by 4.9 % and 3.2 % in NTD students and by 20 % and 25.9 % in ED students, respectively. Energy value of NTD and ED student diets was 2.7 % and 21.4 % higher than the norm, respectively. The differences in parameters values between the groups were statistically significant (p ≤ 0.01). Positive changes were observed in NTD fourth year students meal patterns. However, there was no significant difference between the data on meals frequency and daily food consumption distribution in NTD and ED students. The association between the changes of eating behavior